Mixed Land Use: Concepts, Experiences, and Indicators (Journal of the College of Education for Women, 2026)
The role of mixed land use has become widely prominent and prevalent in urban proposals as a strategy aimed at adding value to the area to distinguish it from areas with separate uses by combining compatible and diverse activities at different levels to createA vibrant environment that meets the needs of the community to enhance the integration and vitality of the place, increase interaction between members of the local community, and encourage daily activities, most importantly walking in public spaces.The appropriate layout of their homes makes the different uses compatible with each other and creates an organized and healthy arrangement to achieve the basic objectives of the planning process (compatibility between mixed land uses). It is necessary to emphasize the achievement of luxury and the provision of basic services.and create a healthy and vibrant community characterized by effectiveness among its members within the city. The city is composed of a complex resulting from the intertwining of functions, multiple uses, and needs according to political, administrative, economic, and social choices, which in turn calls for the practice of